Application of ROMS-SWAN coupled model to simulate hydrodynamic field in Hai Phong - Nguyen, Le Tuan; Nguyen, Thi Khang; Le, Duc Dung; Nguyen, Hoang Anh (Vietnam Journal of Marine Science and Technology, 2022)
ROMS and SWAN models have been used quite commonly in studying hydrodynamics. These are open-source models which are suitable for development research. However, using the ROMS-SWAN coupled model has not been studied and applied much in Vietnam. This paper presents the study and use of the ROMS-SWAN coupled model in the COAWST system to calculate the hydrodynamic field in Hai Phong at a primitive level. The calculation gives quite good results when compared with the measured data. The results of this study are the basis for the application of the COAWST model system to calculate sediment transport.